Tilianin suppresses NLRP3 inflammasome activation in myocardial ischemia/reperfusion injury via inhibition of TLR4/NF-κB and NEK7/NLRP3 - Yin, Suyue; Han, Kaixi; Wu, Di; Wang, Zihan; Zheng, Ruifang; Fang, Lianhua; Wang, Shoubao; Xing, Jianguo; Du, Guanhua (Frontiers in Pharmacology, 2024)
Tilianin, a flavonoid compound derived from Dracocephalum moldavica L., is recognized for its diverse biological functionalities, in particular alleviating myocardial ischemiareperfusion injury (MIRI). There is ample evidence suggesting that the NLRP3 inflammasome has a significant impact on the development of MIRI. In this study, rats undergoing the ligation and subsequent release of the left anterior descending (LAD) coronary artery and H9c2 cardiomyocytes subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) were used to investigate the effects of tilianin on NLRP3 inflammasome and its anti-MIRI mechanisms. Upon reperfusion, the rats were intraperitoneally injected with tilianin at doses of 3, 10, 30 mg/kg. H9c2 cells were treated with tilianin at concentrations of 10, 30, and 50 g/mL. Echocardiography, TTC staining and TUNEL staining demonstrated that tilianin remarkably improved cardiac function and